1
$\begingroup$

Given this differential equation

$x^2y^3+y+(x^3y^2-x)y'=0$

I have to find an integrating factor, such that the equation becomes an exact differential equation.

I am pretty sure that the integrating factor must be $\mu (xy)$, so let $xy=z$.

After some algebra I got this differential equation:

$\mu '(z)(z+1)(y-x)=-2\mu (z)$

I have checked my calculations many times and I am certain, that this equation is correct.

However, I don't know what to do now, since I have my $\mu$ depending on the product $xy$.

How do I get $\mu (z)$? Or am I going in the wrong direction with this attempt?

$\endgroup$
  • $\begingroup$ Are you sure the factor multiplying $y'$ is "$(x^3y^2 - x)$" and not "$(x^3y^2 + x)$"? The problem would simplify in the latter case (or, are you sure the "$x^2y^3 + y$" is correct, or is it "$x^2y^3-y$"?) $\endgroup$ – Michael Nov 16 '15 at 22:36
  • $\begingroup$ @Michael: Yes, I checked it and it is correct the way it's written. $\endgroup$ – de_dust Nov 16 '15 at 22:38
  • 1
    $\begingroup$ An integrating factor $\mu(x,y) = 1/(xy)$ seems to help. $\endgroup$ – Michael Nov 16 '15 at 22:51
1
$\begingroup$

So, you can try multiplying both sides of the equation by $1/(xy)$.

Overall, your method using $\mu(z)$ (for $z=xy$) is correct, but you get a strange result $\mu'(z)(z+1)(y-x)=-2\mu(z)$, and I don't know how you got that. I get a very different answer when using your method. It is indeed a simple ODE for $\mu(z)$, and indeed leads to the same result as just directly multiplying by $1/(xy)$.


I got my answer of multiplying by $1/(xy)$ just by playing around. But you can do it more systematically your way:

Theory: Suppose $a(x,y) + b(x,y)y' = 0$. Multiply by $\lambda(x,y)$ to get: $$ \lambda(x,y)a(x,y) + \lambda(x,y)b(x,y)y'=0$$ We want a function $f(x,y)$ such that: \begin{align} &\partial f/\partial x = \lambda(x,y)a(x,y)\\ &\partial f/\partial y = \lambda(x,y)b(x,y) \end{align} If we find such, we can say $f(x,y(x))=C$. We should have $\frac{\partial^2 f}{\partial x \partial y} = \frac{\partial^2 f}{\partial y \partial x}$. So we want: $$ \frac{\partial [\lambda(x,y)a(x,y)]}{\partial y} = \frac{\partial [\lambda(x,y)b(x,y)]}{\partial x} $$ In this case you are told to try $\lambda(x,y)=\mu(z)$ for $z=xy$ (and $\partial z/\partial x$ and $\partial z/\partial y$ can easily be calculated) and so: $$ \frac{\partial [\mu(z)(x^2y^3 +y)]}{\partial y} = \frac{\partial [\mu(z)(x^3y^2-x)]}{\partial x} $$ Doing the derivatives and simplifying leads to a simple ODE in $\mu(z)$ (with no $x$ or $y$ variables).

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ @de_dust : Were you able to fix the mistakes to get a proper ODE for $\mu(z)$ using your method? You end up within something like $h(z)\mu'(z) + r(z) =0$, with simple $h(z)$ and $r(z)$ functions. $\endgroup$ – Michael Nov 16 '15 at 23:12
  • $\begingroup$ Ok, I can't seem to find the integrating factor by myself. I get $\mu '(z)(x^2y^3+y-x^3y^2+x)=\mu (3x^2y^2-1)-\mu (z)(3x^2y^2+1)$ and after simplifying the term I end up with my equation. $\endgroup$ – de_dust Nov 17 '15 at 0:18
  • $\begingroup$ Could you please explain how you got your solution? $\endgroup$ – de_dust Nov 17 '15 at 0:18
  • $\begingroup$ What are you doing to get your equality? I will modify my answer to give more details. $\endgroup$ – Michael Nov 17 '15 at 6:23
  • 1
    $\begingroup$ Note that $d \mu/dx =(d\mu/d z)(dz/dx)$. $\endgroup$ – Michael Nov 17 '15 at 7:21

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.